Field evaluation of Trichogramma ostriniae (Hymenoptera: Trichogrammatidae) and T. brassicae as biocontrol agents of the European corn borer, Ostrinia nubilalis (Lepidoptera: Crambidae), in fresh market sweet corn - Etilé, Elsa; Cabrera, Paula; Boisclair, Josée; Cormier, Daniel; Todorova, Silvia; Lucas, Éric (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ), 2024)
The efficiency of two Trichogramma species as biocontrol agents against the European corn borer (ECB) Ostrinia nubilalis (Lepidoptera: Crambidae) was investigated under field conditions. Five inundative releases of Trichogramma ostriniae and T. brassicae (Hymenoptera: Trichogrammatidae) were done in sweet corn plots. Ostrinia nubilalis sentinel egg masses were placed on corn plants in order to compare the efficiency of the two Trichogramma species. The parasitism rate of O. nubilalis egg masses by T. ostriniae was 13% higher than egg masses parasitized by T. brassicae. Likewise, the percentage of eggs parasitized per mass by T. ostriniae was significantly higher following two of the five releases. Attacked egg masses showed an average of 29% of eggs parasitized by T. ostriniae, versus 14% of eggs parasitized by T. brassicae. The rate of parasitoid emergence from sentinel egg masses was also significantly higher for T. ostriniae than for T. brassicae. Damages to plants due to ECB did not differ significantly in presence of the two parasitoid species. However, plants in plots receiving parasitoids showed less damage than plants in control plots. Overall, T. ostriniae was clearly more efficient than T. brassicae to parasitized egg masses of O. nubilalis in sweet corn.